Isavuconazole treatment for mucormycosis: a single-arm open-label trial and case-control analysis. Issue 7 (July 2016) - Marty, Francisco M; Ostrosky-Zeichner, Luis; Cornely, Oliver A; Mullane, Kathleen M; Perfect, John R; Thompson, George R; Alangaden, George J; Brown, Janice M; Fredricks, David N; Heinz, Werner J; Herbrecht, Raoul; Klimko, Nikolai; et al.
Summary: Background: Mucormycosis is an uncommon invasive fungal disease with high mortality and few treatment options. Isavuconazole is a triazole active in vitro and in animal models against moulds of the order Mucorales. We assessed the efficacy and safety of isavuconazole for treatment of mucormycosis and compared its efficacy with amphotericin B in a matched case-control analysis. Methods: In a single-arm open-label trial (VITAL study), adult patients (≥18 years) with invasive fungal disease caused by rare fungi, including mucormycosis, were recruited from 34 centres worldwide. Patients were given isavuconazole 200 mg (as its intravenous or oral water-soluble prodrug, isavuconazonium sulfate) three times daily for six doses, followed by 200 mg/day until invasive fungal disease resolution, failure, or for 180 days or more. The primary endpoint was independent data review committee-determined overall response—ie, complete or partial response (treatment success) or stable or progressive disease (treatment failure)—according to prespecified criteria. Mucormycosis cases treated with isavuconazole as primary treatment were matched with controls from the FungiScope Registry, recruited from 17 centres worldwide, who received primary amphotericin B-based treatment, and were analysed for day-42 all-cause mortality. VITAL is registered with ClinicalTrials.gov, number NCT00634049 . FungiScope is registered with ClinicalTrials.gov, number NCT01731353 . Findings: Within the VITAL study, from April 22, 2008, to June 21, 2013, 37 patients with mucormycosis received isavuconazole for a median of 84 days (IQR 19–179, range 2–882). By day 42, four patients (11%) had a partial response, 16 (43%) had stable invasive fungal disease, one (3%) had invasive fungal disease progression, three (8%) had missing assessments, and 13 (35%) had died. 35 patients (95%) had adverse events (28 [76%] serious). Day-42 crude all-cause mortality in seven (33%) of 21 primary-treatment isavuconazole cases was similar to 13 (39%) of 33 amphotericin B-treated matched controls (weighted all-cause mortality: 33% vs 41%; p=0·595). Interpretation: Isavuconazole showed activity against mucormycosis with efficacy similar to amphotericin B. Isavuconazole can be used for treatment of mucormycosis and is well tolerated. Funding: Astellas Pharma Global Development, Basilea Pharmaceutica International.